Systematic Review of Risk and Protective Factors for Revictimization After Child Sexual Abuse. (January 2021) - Scoglio, Arielle A. J.; Kraus, Shane W.; Saczynski, Jane; Jooma, Shehzad; Molnar, Beth E.
Child sexual abuse (CSA) is a widespread public health problem in the United States. It has been associated with multiple long-term deleterious outcomes including revictimization in adulthood. This systematic review of 25 studies synthesizes research examining possible risk and protective factors that might explain the established link between CSA and future victimizations. Specific risk factors identified included co-occurring maltreatment in the home, risky sexual behavior (particularly in adolescence), post-traumatic stress disorder, emotion dysregulation, and other maladaptive coping strategies. Only one protective factor was identified: perceived parental care. The review also revealed considerable variability in definitions and measurement of both CSA and adult victimization, particularly in terms of how researchers conceptualized age. Many of the studies were limited in generalizability by including only college-age women. These findings have clinical and research implications. Public health interventions working to prevent revictimization among CSA survivors can utilize these findings when designing programs. For researchers, the results highlight the need for standardized definitions of both CSA and revictimization, for well-validated and consistent measurement, and for inclusion of additional population groups in future research.